Genital Abnormalities, Hormonal Contraception, and Human Immunodeficiency Virus Transmission Risk in Rwandan Serodifferent Couples. (5th March 2021) - Wall, Kristin M; Karita, Etienne; Nyombayire, Julien; Ingabire, Rosine; Mukamuyango, Jeannine; Parker, Rachel; Brill, Ilene; Price, Matt; Haddad, Lisa B; Tichacek, Amanda; Hunter, Eric; Allen, Susan
Abstract: Background: We explored the role of genital abnormalities and hormonal contraception in human immunodeficiency virus (HIV) transmission among heterosexual serodifferent couples in Rwanda. Methods: From 2002 to 2011, HIV-serodifferent couples who were not using antiretroviral treatment were followed up, and sociodemographic and clinical data were collected, family planning provided, and HIV-negative partners retested. Couples were assessed for genital ulcers; nonulcerative genital sexually transmitted infection (STIs), including gonorrhea, chlamydia, and trichomoniasis; and non-STI vaginal infections, including bacterial vaginosis and candida. Multivariable models evaluated associations between covariates and HIV transmission genetically linked to the index partner. Results: Among 877 couples in which the man was HIV positive, 37 linked transmissions occurred. Factors associated with women's HIV acquisition included genital ulceration in the female partner (adjusted hazard ratio, 14.1) and nonulcerative STI in the male partner (8.6). Among 955 couples in which the woman was HIV positive, 46 linked transmissions occurred. Factors associated with HIV acquisition in men included nonulcerative STI in the female partner (adjusted hazard ratio, 4.4), non-STI vaginal dysbiosis (7.1), and genital ulceration in the male partner (2.6). Hormonal contraception use was not associated with HIV transmission or acquisition. Conclusions: Our findings underscore the need for integrating HIV services with care for genital abnormalities. Barriers (eg, cost of training, demand creation, advocacy, and client education; provider time; and clinic space) to joint HIV/STI testing need to be considered and addressed. Abstract : Our findings underscore the need to improve integration of human immunodeficiency virus (HIV) services with care for genital inflammation, ulceration, and infection, which were associated with HIV risk. Hormonal contraceptive use was not associated with HIV risk in this study.